ANALISIS PENGARUH CAR,NPL,PDN,NIM,BOPO,LDR,DAN SUKU BUNGA SBI TERHADAP ROA - Utomo, Budi Sungkowo (Proceeding SENDI_U, 2015)
This research is performed on order to test the influence of the variable Capital Adequacy Ratio (CAR),Non Performing Loan (NPL), Posisi Devisa Netto (PDN), Net Interest Margin (NIM), BOPO (BiayaOperasional/Pendapatan Operasional), Loan to Deposit Ratio (LDR), and SBI rate toward Return OnAsset (ROA).Methodology research as the sample used purposive sampling, sample was accured 20 BankDevisa in Indonesia. Data analysis with multi liniear regression of ordinary least square and hypothesestest used t-statistic and Fstatistic at level of significance 5%, a clasic assumption examination whichconsist of data normality test, multicolinearity test, heteroskedasticity test and autocorrelation test is alsobeing done to test the hypotheses. During research period show as variabel and data research wasnormal distributed. Based on test, multicolinearity test, heterosskedasticity test and autocorrelation testclassic assumption deviation has no founded, this indicate that the available data has fulfill the conditionto use multi linear regression model. This result of research show that variable PDN and Suku Bunga SBIdid not influence ROA. Variable CAR, NIM, and LDR positive significant influence significant towardROA. Variable NPL and BOPO negative significant influence toward ROA. Prediction capability fromthese seven variable toward ROA is 72% where the balance 28% is affected to other factor which was notto be entered to research model.Keywords: Return On Asset (ROA), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), PosisiDevisa Netto (PDN), Net Interest Margin (NIM), BOPO (Biaya Operasional/PendapatanOperasional), Loan to Deposit Ratio (LDR), and Suku Bunga SBI.